EFFECTS OF EARTHQUAKE MEASURES ON BRICK BUILDINGS ON THE EXTERNAL WALL PROPERTIES - Khaydarova Kamola Khakimovna; Ismatova Dilfuza (Galaxy International Interdisciplinary Research Journal, 2021)
This article is devoted to the study of the effect of monolithic reinforced concrete elements on the temperature of the interior and exterior walls of brick buildings, as well as the development of recommendations for the prevention of condensate formation in the corners of walls.